Pengaruh Pemberian Ekstrak Kacang Kedelai (Glycine max L.) Terhadap Kadar Eritrosit Mencit (Mus musculus) Jantan Galur Swiss Webster yang Dipapar Natrium Nitrit - Tasya Hani Fatwa; Susianti; Anisa Nuraisa Jausal; Sofyan Musyabiq Wijaya4 (Majority, 2023)
Anaemia is defined by the number of red blood cells (erythrocytes) or haemoglobin level is lower than normal. Consumption of food that contained sodium nitrite (NaNO2) could accelerate the breakdown of erythrocytes in the body. Soybean contains iron and protein which trigger the production of new erythrocytes. This study aims to analyze the effect of soybean to the erythrocyte counts of mice induced by sodium nitrite. The method of this study is a post test control only group design with an analytic laboratory experimental type of study. 25 mice were used in this study as the samples which divided into 5 groups. Data analysis was performed by and bivariate analysis with One-Way ANOVA statistical tests. The result of this study indicates that soybean extract has an effect to the increasing of erythrocyte counts on mice induced by sodium nitrite (p=0.000).